NMR study of styrene-butadiene rubber (SBR) and TiO2 nanocomposites - Arantes, Tatiane M.; Leao, Katyuscya V.; Tavares, Maria Ines B.; Ferreira, Antonio Gilberto; Longo, Elson [UNESP]; Camargo, Emerson R. (Elsevier B.V., 2009)
The chemical behavior of styrene-butadiene rubber (SBR) and of the SBR/TiO2 and photodegraded SBR/TiO2 nanocomposites was investigated through nuclear magnetic resonance spectroscopy (NMR) in the solid state with magic angle spinning (MAS). The C-13 cross polarization/magic angle spinning (CP/MAS) routine spectrum allowed us to obtain information on the polymer microstructure and also to evaluate the domain mobilities. The variation contact time and the proton spin-lattice relaxation time in the rotating frame (T,pH) were determinant factors to evaluate the dynamic molecular motion. The NMR spectrum of the nanocomposites was dislocated 5 ppm to higher chemical shift, indicating the presence of a strong interaction between the polymer chains and the TiO2 nanoparticles. The VTC experiment showed a rigid domain in the SBR/TiO2 photodegraded nanocomposite due to cross-linking reactions. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: NMR; Carbon-13 solid state; Nanocomposites; Photodegradation